Antibacterial Activity of Endophytic Fungi Isolated from Betel Leaf (Piper betle) Against Pseudomonas aeruginosa and Staphylococcus aureus - Kintoko Kintoko; Khrisna Agung Cendekiawan; Sapto Yuliani; Siti Nur Hasana; Firdha Aprilia Wardhani (Faculty of Mathematic and Natural Science, Garut University, 2026)
Betel leaf (Piper betle) contains antibacterial compounds such as flavonoids, saponins, and alkaloids. Endophytic fungi within plant tissues can produce similar bioactive metabolites. This study aimed to isolate, identify, and evaluate the antibacterial activity of endophytic fungi from young betel leaves against Pseudomonas aeruginosa and Staphylococcus aureus. This was experimental research. Endophytic fungi were isolated from young betel leaves on Potato Dextrose Agar (PDA) and identified macroscopically and microscopically. Antibacterial activity was tested using the paper disk agar diffusion method. Three endophytic fungal isolates were obtained: Isolate 1 (Trichoderma sp.), Isolate 2 (Rhizoctonia sp.), and Isolate 3 (Fusarium sp.). Against P. aeruginosa, Isolate 2 produced an average inhibition zone of 7.33 mm, and Isolate 3 produced 8.00 mm. Against S. aureus, Isolate 1 produced 7.33 mm and Isolate 3 produced 7.33 mm. No inhibition was observed for the negative control (DMSO). Endophytic fungi from betel leaves, particularly isolates resembling Rhizoctonia sp., Fusarium sp., and Trichoderma sp., show weak to moderate antibacterial activity against P. aeruginosa and S. aureus under the tested conditions. Further studies using molecular identification and purified extracts are recommended.